2003
DOI: 10.1124/jpet.102.047563
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Growth Hormone-Releasing Peptides Ghrelin and Growth Hormone-Releasing Peptide-6 with the Motilin Receptor in the Rabbit Gastric Antrum

Abstract: The structural relationship between the motilin and the growth hormone secretagogue receptor (GHS-R), and between their respective ligands, motilin and ghrelin, prompted us to investigate whether ghrelin and the GHS-R agonist growth hormonereleasing peptide-6 (GHRP-6), could interact with the motilin receptor. The interaction was evaluated in the rabbit gastric antrum with binding studies on membrane preparations and with contraction studies on muscle strips in the presence of selective antagonists under condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 42 publications
(50 reference statements)
2
33
0
Order By: Relevance
“…This suggests that the effects on food intake and gastric emptying are mediated via different pathways. Previous studies have shown that the starvation signal and the effect on motility by ghrelin are relayed to the brain via vagal afferents (Masuda et al, 2000;Date et al, 2002;Fujino et al, 2003), whereas the effect on motility may also depend upon activation of peripheral receptors (Depoortere et al, 2003Kitazawa et al, 2005;Xu et al, 2005). Selective up-and/or down-regulation of central and peripheral receptors may determine the final effect of exogenous ghrelin on food intake and gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the effects on food intake and gastric emptying are mediated via different pathways. Previous studies have shown that the starvation signal and the effect on motility by ghrelin are relayed to the brain via vagal afferents (Masuda et al, 2000;Date et al, 2002;Fujino et al, 2003), whereas the effect on motility may also depend upon activation of peripheral receptors (Depoortere et al, 2003Kitazawa et al, 2005;Xu et al, 2005). Selective up-and/or down-regulation of central and peripheral receptors may determine the final effect of exogenous ghrelin on food intake and gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rodents, although specific phase III-like contractions were observed every 15 min in the fasted state (7,48), many reports claimed that administration of motilin or a motilin agonist failed to stimulate contraction of rat intestinal muscle strips and gastric emptying. For example, Depoortere et al (4,5) found that motilin did not accelerate rat gastric emptying and transit, and they suggested that motilin and its receptor do not exist or are nonfunctional in these species. Moreover, although several research groups, including our group, have tried to determine the sequence of rat motilin and motilin receptor, no convincing results have been reported so far (1,13), and Peeters (34) described rats and mice as natural motilin and motilin receptor knockouts.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin stimulates the migrating motor complex, resulting in increased gastric emptying and upper GI tract motility in a variety of species (Fujino et al, 2003;Tack et al, 2006;Wang et al, 2007). Despite 50% structural homology between ghrelin and the prokinetic peptide hormone motilin, the activity of these two hormones has been shown convincingly to function via distinct receptors (Depoortere et al, 2003;Sanger, 2008). The ability to stimulate hunger, FI, and GI motility suggests that ghrelin agonists may represent an attractive and unique therapeutic strategy for the treatment of motility disorders (Sanger and Alpers, 2008), such as diabetic and idiopathic gastroparesis, postoperative ileus, opiate-induced bowel dysfunction, and chronic constipation of idiopathic origin (Murray et al, 2005;Tack et al, 2005;Levin et al, 2006;Qiu et al, 2008b,c).…”
mentioning
confidence: 99%